Centro comunitario para el desarrollo cultural del municipio de Puerto López – Meta (2020)
This project starts from the analysis, synthesis and data collection of the research on the municipality of Puerto López - Meta, which presents problems in the sociocultural field, loss of identity and social exclusion due to insufficient equipment that can promote and develop activities. social, educational and cultural. Faced with this need, it was decided to propose the architectural and urban design of the "Community Center for Cultural Development of the municipality of Puerto López - Meta" to provide a solution to the current problem through connectivity, articulation and functionality with activities as important as tourism. , commerce, cultural activity, taking advantage of the natural landscape for sport and enjoyment of the inhabitants of the municipality. The property to intervene is located in the 6th of April neighborhood, at the intersection of 10th street with 7th street and 9th street with 10th street; this being a characteristic place of the municipality. The architectural proposal of the center proposes training, production and dissemination spaces with spaces designed for the promotion of various activities such as workshops, exhibition rooms, administration services, sanitary services, vertical and horizontal circulation services, rehearsal rooms, classrooms , library, toy library, museum, cafeterias, an auditorium, recreational games, gymnasium, parks, green areas and leisure areas that link the community, the scale of the sector is respected and the project is integrated with its nature.